The Influence of Intellectual Ability on Lecturers' Performance and Competencies - Mochammad Munir Rachman; Ch . Menuk Sri Handayani; Sugijanto Sugijanto (Universitas Airlangga, 2022)
Objective: The main objective of this study is to analyze the importance of intellectual abilities in increasing the role of competence and strengthening the performance of lecturers in the management study program at a private university in Surabaya. Design/Methods/Approach: The study utilizes 200 samples obtained by distributing questionnaires to respondents. The explanatory method makes it possible to measure confirmatory factor analysis and SEM analysis to test the model. Finding: The results indicate that intellectual ability has a significant effect on lecturer competence and indirect positive effect on performance. However, the indirect effect is less strong than its direct effect on performance. These results indicate that they have a logical, inspirational, creative, and innovative mindset in carrying out the